Introductory business statistics - Holmes, Alexander; Illowsky, Barbara; Dean, Susan; OpenStax College; BC Open Textbook Project; BCcampus (OpenStax College, Rice University, 2017)
"Introductory Business Statistics is designed to meet the scope and sequence requirements of the one-semester statistics course for business, economics, and related majors. Core statistical concepts and skills have been augmented with practical business examples, scenarios, and exercises. The result is a meaningful understanding of the discipline, which will serve students in their business careers and real-world experiences"--BC Campus website.
Sampling and data -- Descriptive statistics -- Probability topics -- Discrete random variables -- Continuous random variables -- The normal distribution -- The central limit theorem -- Confidence intervals -- Hypothesis testing with two samples -- The chi-square distribution -- F distribution and one-way ANOVA -- Linear regression and correlation -- Statistical tables -- Mathematical phrases, symbols, and formulas -- Index
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Includes bibliographical references and index.
PDF, revision IBS-2017-000(11/17)-LC (viewed 16 January 2017).
Keywords: Commercial statistics -- Textbooks; Statistics -- Textbooks; Electronic books